(untitled) (The International Journal for Scientific Research, 2025)
This study aimed to investigate the impact of learners’ cognitive style (impulsive/reflexive) in a gamified e-learning environment on enhancing the educational well-being of middle school students. The study followed a quasi-experimental approach, where quantitative data were collected and analyzed. The sample consisted of 60 students from Imam Al-Nawawi School in Al-Laith Governorate during the academic year 1446 AH. These students were randomly selected from the third intermediate grade to form the experimental groups under investigation. The results revealed a statistically significant difference between the two experimental groups in the post-measurement of educational well-being. The findings indicated that students with a reflexive cognitive style outperformed their impulsive counterparts, with an average score of (121.27) compared to (114.23) for impulsive students. Additionally, the calculated t-value (9.379) was greater than the tabulated t-value (1.98) at a significance level of (0.05) and a degree of freedom of (58). This led to the rejection of the null hypothesis and the acceptance of an alternative hypothesis confirming the presence of statistically significant differences in favor of the reflexive cognitive style. The study recommended designing gamified e-learning environments that consider individual differences in learners’ cognitive styles.